Conceptual Reflections on Ethics for International Research Collaborations in Disaster Impacted Areas from the Experiences in Indonesia, New Zealand and Japan - Christopher Gomez (Universitas Muhammadiyah Surakarta, 2014)
The present contribution is by no means a first attempt at considering the ethics in human activities, interactions in disaster impacted areas, but it is more the case of looking at 'international research' that present a very particular difficulty for ethics: the notion of trans-boundary, multi-dimensional idea of one group not really belonging within another, but which will perform functions inside this second group and eventually alter, modify some of the original organs. This paper explain the reflections of the ethical consideration of international research collaboration in disaster impacted areas which are emerged from the experiences in Indonesia, New Zealand and Japan.